NAVIGATING SERVICE INNOVATION: INVESTIGATING THE STAGES OF INNOVATION PROCESS IN TELECOMMUNICATION INDUSTRY - Difla Dhea Fiya; Anjar priyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research explored the stages of service innovation within the telecommunications industry, specifically examining PT Telkom Indonesia Datel Temanggung. Using a qualitative approach that included observation and interviews with five employees, the research identified a six-stage process for service innovation: opportunity identification, idea management, concept development, pilot test, launch, and learning. The results highlighted significant challenges faced during the innovation process and emphasized the importance of customer involvement. Additionally, service innovation at PT Telkom had crucial managerial implications, requiring careful evaluation to ensure profitability and customer satisfaction. Managers must navigate the innovation timeline to balance stakeholder impact and avoid employee burnout. Phased rollouts and targeted marketing were recommended strategies to keep customers informed and engaged throughout the innovation process.